Karakteristik Biopelet Karbonisasi Biomassa berbasis Daun Jati dan Jagung menggunakan Perekat Tanah Liat - Ropiuidn, Ropiudin; Toibah, Toibah; Dwiasi, Dian Windy; Syska, Kavadya (Jurnal Agritechno, 2025)
Biomass carbonization plays a vital role in the production of biopellets as a sustainable and environmentally friendly energy source. This study aimed to evaluate the physicochemical characteristics of carbonized biopellets, including density, moisture content, ash content, volatile matter, combustion rate, and mechanical durability. The biopellets were produced from a mixture of teak leaves, corn cobs, and corn stalks, with clay as a binder, and subjected to carbonization under different formulations to assess their influence on final product quality. The experimental design employed a Completely Randomized Design (CRD) with nine treatment combinations and three replications, resulting in a total of 27 experimental units. The treatments consisted of variations in raw material composition (K1, K2, K3) and clay binder proportions (P1, P2, P3). Analyses included physical, chemical, thermal, and durability assessments. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Results indicated that the carbonized biopellets had density values ranging from 0.49 to 0.56 g/cm³, moisture content from 5.34% to 6.82%, ash content from 20.38% to 34.24%, volatile matter from 66.82% to 79.88%, combustion rate from 0.03 to 0.05 g/min, and mechanical durability ranging from 43.72% to 55.03%. The composition of raw materials significantly influenced most parameters, except combustion rate and durability. Meanwhile, binder proportion had a highly significant effect on all parameters except for durability, which showed a significant effect. Based on the results, the carbonized biopellets met the SNI 8021-2014 standard requirements for moisture and volatile matter, while density and ash content were outside the specified limits.